Comparison of surgical outcomes of lumbar disc herniation using local anesthesia and epidural anesthesia: A meta-analysis. Issue 33 (14th August 2020) - Wang, Wei; Ni, Bin-bin; Shen, Hao; Lu, Hua
Abstract : Abstract: We performed this meta-analysis to evaluate the effects of epidural anesthesia and local anesthesia on the surgical outcomes of lumbar disc herniation (DH). Electronic databases including PubMed, EMBASE, Cochrane Library, and the Chinese Academic Journal Full-text Database were searched to identify randomized controlled trials (RCTs) that reported on the effects of local anesthesia and epidural anesthesia in lumbar DH surgical management. Evaluation indicators included: onset time of anesthesia, patient satisfaction, and the rate of adverse effects. There were 6 RCTs with a total of 606 patients in this meta-analysis: 274 cases in the local anesthesia group and 332 in the epidural anesthesia group. This meta-analysis demonstrated that the epidural anesthesia group had a better analgesic effect, a lower adverse effect rate (mean difference [MD] = 0.21, 95% confidence interval [CI] [0.08, 0.54], P  = .001) and a better satisfaction rate: (MD = 6.54, 95% CI [2.77, 15.45], P  < .0001). The duration of anesthesia was not statistically significant. Epidural anesthesia is a better choice for lumbar DH surgery compared to local anesthesia.